Discovering the still unexplored arachnofauna of the National Park of Dadia-Lefkimi-Soufli, NE Greece: a taxonomic review with description of new species - Komnenov, Marjan; Pitta, Eva; Zografou, Konstantina; Chatzaki, Maria (Zootaxa, 2016)
The National Park of Dadia in NE Greece (Thrace) was established as a nature reserve in 1980, mainly due to its great diversity in birds of prey. Since then many studies have taken place, focusing on other birds, reptiles, amphibians and some invertebrates (grasshoppers, beetles and butterflies), but up to now none was conducted on spiders. The aim of the present paper was to create the first extensive checklist on the spiders of this important natural reserve. For this purpose, pitfall traps were set in 15 sites located in and around the National Park, resulting in a large spider collection. The results of the taxonomical revision of this collection are here presented, giving rise to 132 species in total, which belong to 24 families. Of them, 11 species (Centromerus valkanovi Deltshev, 1983, Crosbyarachne silvestris (Georgescu, 1973), Ipa terrenus (L. Koch, 1879), Sintula spiniger (Balogh, 1935), Tenuiphantes floriana (van Helsdingen, 1977), Alopecosa taeniopus (Kulczyñski, 1895), Liocranum rupicola (Walckenaer, 1830), Zodarion turcicum Wunderlich, 1980, Gnaphosa modestior Kulczyñski, 1897, Philodromus krausi Muster & Thaler, 2004, Cozyptila thaleri Marusik & Kovblyuk, 2005) are new records for the Greek territory. Seven species (Dysdera kati sp. n., Dysdera krisis sp. n., Harpactea ice sp. n., Harpactea wolfgangi sp. n.—Dysderidae, Phrurolithus thracia sp. n.—Phrurolithidae, Zodarion beroni sp. n.—Zodariidae, Drassyllus dadia sp. n.—Gnaphosidae) are here proposed as new species for science.